Lack of professional practices of fifth-year students from Modern Language major and its effects when performing on their first job, Foreign Language Department, University of El Salvador, year 2014 - García Torres, Cecilia Ester
The true knowledge is achieved when the learning process is completed and the information becomes action” (Swami Vivekananda). “Professional Practice is where students are required to extend their knowledge and skills within a practical environment”. A country needs to have future professionals who since the beginning are able to face confidently, competitively and professionally the different challenges of a changeable society. A simple way to prepare these professionals is through providing them with the opportunity to experience in their area of specialization within their particular professional field. This practice should be done before they are launched to the real labor world with a professional supervision. The lack of this practice in a major might provoke some negative effects that lead students feel unconfident, frustrated and incapable to respond to different real situations when performing on their first job.